2018
DOI: 10.15744/2393-9060.5.303
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Antioxidant, Anti-Inflammatory and Gastroprotective Abilities of Mango (Magnifera indica) Leaf Extract and Mangiferin

Abstract: Mango (Mangifera indica Linn.) trees have been cultivated and grown in Southern and Eastern India for thousands of years and have slowly spread all over the world. For over 4,000 years various parts of mango trees including leaf and fruit pulp have been extensively used in Ayurvedic and Unani medicines. Mango pulp and leaves contain diverse health promoting chemical constituents including mangiferin, a natural polyphenol of C-glycosylxanthone structure, with diverse pharmacological/physiological activities inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…When converted to dried weights of initial materials, contents of mangiferin were identified within a range from 8.71 to 81.82 mg/g dried powder, which is equal to 0.87 to 8.18%. These results were similar to but slightly lower than those reported by Stohs et al [29], who reported that mangiferin contents in mango leaves varied from 2 to 15% depending on varieties and geographic sources. In our study, the mangiferin content of young dark reddish brown leaves was 81.82 mg/g, in accordance with the report of Parafati et al [30], who also investigated red-colored mango leaves and reported the concentration to be 84.52 mg/g dried weight.…”
Section: Effects Of Maturity Stages On Mangiferin Contents Of Mango L...supporting
confidence: 90%
See 1 more Smart Citation
“…When converted to dried weights of initial materials, contents of mangiferin were identified within a range from 8.71 to 81.82 mg/g dried powder, which is equal to 0.87 to 8.18%. These results were similar to but slightly lower than those reported by Stohs et al [29], who reported that mangiferin contents in mango leaves varied from 2 to 15% depending on varieties and geographic sources. In our study, the mangiferin content of young dark reddish brown leaves was 81.82 mg/g, in accordance with the report of Parafati et al [30], who also investigated red-colored mango leaves and reported the concentration to be 84.52 mg/g dried weight.…”
Section: Effects Of Maturity Stages On Mangiferin Contents Of Mango L...supporting
confidence: 90%
“…In contrast, this was higher the result of Loan et al [33], who identified the content to be 9.51 mg/g. The differences might be explained via the fact that mangiferin constituents in mango leaves are largely dependent on origin and plant variety [28,29].…”
Section: Effects Of Maturity Stages On Mangiferin Contents Of Mango L...mentioning
confidence: 99%
“…4 Values are expressed as mean ± standard deviation (S.D.) 5 Different superscript letters in the column indicate differences are significant at p < 0.05.…”
Section: Phenolic Yield and Total Phenolic Contentsmentioning
confidence: 99%
“…The bioactive effects reported for M. indica include antioxidant activity, anti-inflammatory, antipyretic, antibacterial, antiviral, antimicrobial, and anticancer, as well as hepatoprotective and gastroprotective properties, in addition to immunomodulatory and lipid-lowering drug effects [2][3][4][5]. Particularly, it has been reported that mango exhibits antiproliferative activity in MDA-MB-231 adenocarcinoma breast cell lines, HepG2 liver, and HL-60 leukemia cancer cells [6], as well as antitumoral effects on MCF-7 breast carcinoma cells [7], Molt-4 leukemia, A-549 lung, LnCap prostate, and SW-480 colon cancer cells [8].…”
Section: Introductionmentioning
confidence: 99%
“…The plant is used extensively in religious and social ceremonies and for nutrition and therapeutic purposes. According to Stohs et al (2018), the leaves are employed in Hinduism on practically all significant occasions, including worship and wedding rituals [ 19 ]. According to Laurindo et al (2015), the fruit’s outer peels are used as cosmetics, and Namngam and Pinsirodom (2017) reported that the seeds are used to make beauty creams.…”
Section: Introductionmentioning
confidence: 99%